Communicating safety with drivers via dynamic message signs. (August 2021) - Kassens-Noor, Eva; Savolainen, Peter T.; Gates, Timothy J.; Cai, Meng; Deaminada, Travis
Highlights: Emotions in safety messaging have a significant impact on self-reported driving behavior. Messages mentioning cell phone use show high recall. Positively themed messages were recalled more often than others. Consequences had no significant effect on self-reported driving behavior. Abstract: In recent years numerous transportation agencies have begun displaying creative safety messages like "get your head out of your apps" on dynamic message signs (DMS). DMS have been used traditionally to provide real-time information about travel times, weather conditions, construction, and incidents. Applying emotional and consequential concepts from protection motivation theory, which has a track record of leading to behavioral changes from public awareness campaigns, this study evaluates how the use of safety messages on DMS impacts driver perceptions. We find that emotions, but not consequences, impact self-reported driving behavior. Further, while drivers reported negative emotions would change their driving habits, positive messages were recalled far more often. Cell phone related messages were recalled most frequently despite being rarely displayed along roadways in Michigan where the study is conducted. Thus, the results support the use of positively themed messages with consequences that drivers perceive as realistic.